Assessing the Conductivity of Wires Under Different Coating Types - Iroka, Jude; Akpienbi, Isaac Oritsejubemi (Darul Yasin Al Sys, 2024)
This study investigates the impact of different types of coatings (A, B, C and D) on the conductivity of wire. The experiment employed a one-way ANOVA followed by post hoc analysis using Tukey’s Honest Significant Difference (TukeyHSD) test to determine significant differences between the coatings. The results indicated that coatings A, B, C and D have a significant effect on wire conductivity (F (3, 16) =29.79, p<0.05). Post hoc analysis revealed significant differences between the following pairs of coatings: C-A, D-A, C-B, and D-B (p<0.05). These findings suggest that the choice of coating significantly impacts wire conductivity and may guide manufacturers in selecting coatings based on specific conductivity requirements.